Screening Cation and Anion of Ionic Liquid for Dissolution of Silicon Dioxide using COSMO-RS - Muhammad Suhaimi, Man; Mohd Amirulmukmin, Abdullah; Syamsul Bahari, Abdullah; Zulkefli, Yaacob (Informatics Publishing Limited, 2017)
Objectives:Silicon dioxide (SiO2) is one of the common oilfield scales which is hardest scale to dissolve and there is no specific commercial chemical scale removal to dissolve SiO2. The purpose of this study to screens Ionic Liquids (ILs) that will be used in dissolution of SiO2due toscale problem in oilfield. Methods/StatisticalAnalysis:COSMO-RS since then has become a widely used and fast method for the prediction and screening of ionic liquid properties, is used for sigma profile, sigma potential and solvent capacity for metal dissolution. The best cation and anion have been chosen based on sigma profile, sigma potential and the high solvent capacity from COSMO-RS findings. Findings: Ammoniumcation and sulfate anion is the best combination with highest amount of SiO2 capacity is 7.832x1010. Ammonium sulfate is the possible ionic liquid to dissolve SiO2 scale in oilfield.